2022
DOI: 10.21037/atm-22-4091
|View full text |Cite
|
Sign up to set email alerts
|

Impact of individualized pharmaceutical care on efficacy and safety of opioid-tolerant outpatients with cancer pain: a multicenter randomized controlled trial

Abstract: Background: Managing cancer pain is a growing challenge. Individualized pharmaceutical care is particularly important for opioid-tolerant outpatients due to variation in terms of their knowledge about pain, treatment adherence, and risk of experiencing inadequate analgesia and severe adverse events. This study aimed to determine the influence of individualized pharmaceutical care on outcomes in opioid-tolerant outpatients with cancer pain. Methods:A multicenter, open-label, randomized, controlled study was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Different levels of graded pharmaceutical care measures are implemented at different stages of the disease,30 which can identify and intervene in drug-related problems in a timely manner in the treatment of COPD and other diseases 31. In addition, it enables correct understanding of the connotation of pharmacy services, forming good values, encouraging innovative strategies such as personalised pharmaceutical care to improve patient satisfaction and improve prognosis 32–34…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different levels of graded pharmaceutical care measures are implemented at different stages of the disease,30 which can identify and intervene in drug-related problems in a timely manner in the treatment of COPD and other diseases 31. In addition, it enables correct understanding of the connotation of pharmacy services, forming good values, encouraging innovative strategies such as personalised pharmaceutical care to improve patient satisfaction and improve prognosis 32–34…”
Section: Resultsmentioning
confidence: 99%
“…31 In addition, it enables correct understanding of the connotation of pharmacy services, forming good values, encouraging innovative strategies such as personalised pharmaceutical care to improve patient satisfaction and improve prognosis. [32][33][34]…”
Section: Analysis Of Abstractmentioning
confidence: 99%
“…Clinical pharmacists provide pharmaceutical care such as dispensing, training and teaching, checking prescriptions, drug monitoring, making treatment plans, patient education, pharmacy consultation, joining clinical rounds, medication guidance and pharmaceutical monitoring ( Guo et al, 2020 ). A systematic review ( Penm et al, 2014a ) and several empirical researches ( Shao et al, 2017 ; Xie et al, 2020 ; Ding et al, 2022 ) in China reported that pharmaceutical care saved medical costs and positively influenced health outcomes by increasing appropriate use of medication, patient knowledge, quality of life, adherence and reducing patient length of hospitalization. In recent years, the Chinese authorities strongly support the implementation of pharmaceutical care.…”
Section: Introductionmentioning
confidence: 99%